Temporalidade do trabalho e do não trabalho: efeitos e sentidos da regulamentação jurídica - Nara Abreu Santos (2019)
Labour Law regulates the relationship between time and work in contemporary society, it organizes individual and collective experiences, and it also affects in both professional and personal lives. Thus, this research proposes a bibliographic and legislation study on the new morphology of work based on time as a category, as well as on the nature of non-working times, with the aim of investigating if and how can legal standards assure effective free time. Initially, in a panoramic way, it follows the path from the establishment of standard working time until its current dismantling in the context of global capitalism, which is characterized by, in legal terms, flexibility and precariousness. Furthermore, it carries out a thorough study on the division of social times into two groups: working times and non-working times. This research was held through theoretical reflections, in the sense of revisiting concepts and meanings, that revealed even gender inequalities. In conclusion, if the regulatory model of working time, in its three dimensions – extension, intensity, and distribution – complies with the political values and principles of a community, this research demonstrates that modulations of working times and non-working times have not been operated according to basic human needs, but in a convenient way to satisfy the production and consumption demands of the capitalist system. Finally, in times of retrograde step in social terms, to understand the role and relevance of having control over someone’s own time is indispensable for ensuring individual health, inside and outside of the employment relationship.